A digital mathematical storytelling framework for supporting students' mathematical literacy: A systematic literature review - Amalia, Rizki; Herman, Tatang; Jupri, Al; Martadiputra, Bambang Avip Priatna (Indonesian Journal of Science and Mathematics Education, 2026)
Despite increasing attention to mathematical literacy, mathematics instruction remains largely procedural and often fails to connect mathematical concepts with meaningful real-life contexts. This study aimed to synthesise existing evidence and propose a Digital Mathematical Storytelling (DMS) framework for supporting students' mathematical literacy through a Systematic Literature Review (SLR). A SLR was conducted in accordance with the PRISMA 2020 guidelines. From an initial pool of 186 records, 28 studies met the inclusion criteria and were analysed using thematic synthesis. The analysis involved extracting study characteristics, conducting open coding, identifying recurring pedagogical patterns, and synthesising these patterns into higher-order themes. The synthesis resulted in a DMS framework comprising three interconnected dimensions: narrative construction, mathematical inquiry, and reflective engagement. These dimensions collectively provide a pedagogical pathway that supports students in formulating, employing, and interpreting mathematics in authentic contexts, consistent with the OECD mathematical literacy framework. Unlike previous studies that have examined storytelling, inquiry, or reflection separately, the proposed framework integrates these three pedagogical dimensions into a coherent approach for supporting students' mathematical literacy. The framework contributes both theoretically, by providing an integrated conceptual foundation for DMS, and practically, by guiding the design of literacy-oriented mathematics instruction and informing future empirical research.